THE PROCESS OF PROCURING GOODS AND SERVICES USING THE TENDER METHOD AT THE LOGISTICS DIVISION ON THE HEAD OFFICE OF PT BRI ASURANSI INDONESIA JAKARTA - Dewi, Nadira Sandra; Budiatmo, Agung (International Journal Multidisciplinary (IJMI), 2024)
Tender procurement is an activity that is carried out openly to meet the demand for needs within a company by considering considerations in terms of quality, quantity, delivery time, as well as price and is usually used for procurement in large quantities and values which are also complex. The aim of this research is to determine the process of procuring goods and services using the tender method and the obstacles in implementing the procurement process using the tender method at PT. BRI Asuransi Indonesia Head Office Jakarta. This research uses a descriptive qualitative research method using data collection techniques, namely interviews, observation and documentation, then obtaining data sources from primary data and secondary data which are processed using data analysis techniques through reduction, presentation and drawing conclusions as well as applying triangulation of source data and time. The results of this research indicate that the implementation of the procurement process using the tender method at PT. BRI Asuransi Indonesia Jakarta Head Office has complex procedures and is guided by the procedures stated in the decision letter. The stages start from the distribution of announcements, the analysis process, document collection, document assessment, clarification and negotiation, announcement of winners, to the issuance of purchase order documents and work orders. The process of tender procurement has not been carried out effectively because there are still obstacles found in the process, namely (1) there is a process that is carried out manually and (2) the length of time for the process of making agreement documents. The company can overcome these obstacles by implementing an e-procurement system to speed up the process, accompanied by providing outreach regarding how to use it and then also improving coordination between the compliance and risk management division and the legal team related to creating applicable document templates to save inspection time.Keywords : Process, Procurement, Tender.